Thrombolytic therapy for acute stroke 2026-02-15T23:27:51+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Lyden, Patrick D. (Springer, 2015)

(untitled)
Thrombolytic therapy is now reaching patients in a variety of settings all over the world. Formerly in the domain of sub-specialists, thrombolytic therapy now rests in the realm of emergency medicine, intensive care, vascular, and neurocritical physicians. Extensively updated from previous editions, Thrombolytic Therapy for Acute Stroke, Third Edition is a practical and thorough reference to all those caring for acute stroke patients. Chapters feature new data, technologies and cases offering guidance to treating acute stroke patients ? with or without thrombolytic therapy. Physicians looking to utilize thrombolytic therapy for acute stroke will find this text an invaluable resource